1995
DOI: 10.1016/s1078-5884(05)80131-5
|View full text |Cite
|
Sign up to set email alerts
|

Lupus anticoagulant in patients with peripheral vascular disease: A prospective study

Abstract: The high prevalence of LAC in patients with peripheral vascular disease and the associated increased risk of early graft thrombosis may justify routine testing by DRVVT prior to reconstructive vascular surgery. Treatment of these patients with antiplatelet agents or formal anticoagulation perioperatively should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Proteins involved in, stimulated by or associated with thrombosis have been the biomarkers most commonly assessed in AAA. Markers evaluated include fibrinogen, D-dimer, homocysteine, tissue plasminogen activator, von Willebrand factor, soluble thrombomodulin, plasminogen activator inhibitor-1, activated protein C-protein C inhibitor complexes, plasmin-antiplasmin complexes, P-selectin, thrombin-antithrombin III complex and fibrinogen degradation products [49-58,61-73,75]. The association between plasma fibrinogen and AAA has been studied extensively, with 5 of 10 investigations reporting higher concentrations in patients with AAA (Table I) [49-58].…”
Section: Circulating Biomarkers and Their Association With Aaa Presenmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins involved in, stimulated by or associated with thrombosis have been the biomarkers most commonly assessed in AAA. Markers evaluated include fibrinogen, D-dimer, homocysteine, tissue plasminogen activator, von Willebrand factor, soluble thrombomodulin, plasminogen activator inhibitor-1, activated protein C-protein C inhibitor complexes, plasmin-antiplasmin complexes, P-selectin, thrombin-antithrombin III complex and fibrinogen degradation products [49-58,61-73,75]. The association between plasma fibrinogen and AAA has been studied extensively, with 5 of 10 investigations reporting higher concentrations in patients with AAA (Table I) [49-58].…”
Section: Circulating Biomarkers and Their Association With Aaa Presenmentioning
confidence: 99%
“…Markers evaluated include fibrinogen, D-dimer, homocysteine, tissue plasminogen activator, von Willebrand factor, soluble thrombomodulin, plasminogen activator inhibitor-1, activated protein C-protein C inhibitor complexes, plasmin-antiplasmin complexes, P-selectin, thrombin-antithrombin III complex and fibrinogen degradation products [49-58,61-73,75]. The association between plasma fibrinogen and AAA has been studied extensively, with 5 of 10 investigations reporting higher concentrations in patients with AAA (Table I) [49-58]. The studies showing no association generally included very small numbers of patients [51,54,57,58] except for one investigation carried out exclusively in smokers [56].…”
Section: Circulating Biomarkers and Their Association With Aaa Presenmentioning
confidence: 99%
See 1 more Smart Citation
“…The platelet neutralization procedure in the DRVVT was found in 26 out of the 60 (43%) vascular patients compared with none of the 20 general surgical controls [30], though a later survey found a lower 4% prevalence of LA in 150 patients with peripheral vascular disease [31].…”
Section: Peripheral Vascular Disease and Antiphospholipid Antibodiesmentioning
confidence: 88%
“…No association of anti-␤ 2 GPI and coronary atherosclerosis was found in a cross-sectional study of 97 subjects [33]. A study of 60 peripheral vascular disease patients found the LA in 43% versus 0% of controls [34].…”
Section: Prevalence Of Apl In Arterial Thrombosismentioning
confidence: 92%